2018
DOI: 10.2147/cmar.s170083
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bone metastasis and factors contributing to its development and prognosis in newly diagnosed renal cell carcinoma: a population-based study

Abstract: PurposeThe purpose of this study was to assess the incidence of and the risk factors and prognostic factors for bone metastasis (BM) in initial metastatic renal cell carcinoma (RCC) based on a large population analysis.Patients and methodsData were obtained for a total of 45,824 RCC patients recorded in the database of the Surveillance, Epidemiology, and End Results program of the National Cancer Institute between 2010 and 2014. Multivariate logistic and Cox regression analyses were used to identify the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
5
27
1
Order By: Relevance
“…Prognostic factors in the cancer patients with distant metastases have been widely studied [14][15][16].…”
Section: Ivyspringmentioning
confidence: 99%
“…Prognostic factors in the cancer patients with distant metastases have been widely studied [14][15][16].…”
Section: Ivyspringmentioning
confidence: 99%
“…For example, Norgaard et al [4] reported that the 1-year and 5-year survival rates were approximately 47% and 3%, respectively, for PCa patients with bone metastases at initial diagnosis. Apart from PCa, breast and kidney cancers also have a propensity of metastasizing to the bones; and patients with disease that remains confined to the skeleton have a better prognosis than do those with synchronous multiple sites of involvement [8, 9]. However, the sites of synchronous extra-skeletal metastases, e.g., the lung, brain, and liver, and the associated prognostic outcomes in de novo PCa patients with bone metastases have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Bone is a common organ for distant metastasis [3,4]. In patients with esophageal cancer, bone metastasis (BM) was reported as the third common metastatic site [5,6].…”
Section: Introductionmentioning
confidence: 99%